2007
DOI: 10.1021/jf071771q
|View full text |Cite
|
Sign up to set email alerts
|

Antiatherogenic Effect of Isoflavones in Ovariectomized Apolipoprotein E-Deficient Mice

Abstract: The consumption of isoflavone-containing foods such as soybean and soybean products has been reported to have beneficial effects on the cardiovascular system in postmenopausal women. The present study was carried out to examine the mechanism underlying the beneficial effects of isoflavones in apolipoprotein (apo) E-deficient mice subjected to ovarian resection. Compared with sham-operated mice, ovariectomized mice had a larger arterial lesion area in the aortic root. Feeding the ovariectomized mice an isoflavo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 37 publications
0
5
0
Order By: Relevance
“…We examined the mechanism underlying the beneficial effects of isoflavones in apoEÀ/À mice subjected to ovarian resection. 135) Compared with sham-operated mice, the ovariectomized mice had larger arterial lesion areas in the aortic root. Feeding the ovariectomized mice an isoflavone-containing diet (0.055 mg/kJ of total isoflavones/cal of diet) reduced the sizes of these lesions more than did feeding them an isoflavone-free diet.…”
Section: Mineralsmentioning
confidence: 96%
“…We examined the mechanism underlying the beneficial effects of isoflavones in apoEÀ/À mice subjected to ovarian resection. 135) Compared with sham-operated mice, the ovariectomized mice had larger arterial lesion areas in the aortic root. Feeding the ovariectomized mice an isoflavone-containing diet (0.055 mg/kJ of total isoflavones/cal of diet) reduced the sizes of these lesions more than did feeding them an isoflavone-free diet.…”
Section: Mineralsmentioning
confidence: 96%
“…26) This preceding work indicates a beneficial effect of estrogen on the development of atherosclerosis. In contrast, it has been reported that estrogen accelerates breast cancer, 27) and that proanthocyanidins derived from grapes exert a beneficial effect on breast cancer by suppressing the synthesis of estrogen by inhibiting aromatase activity.…”
Section: Discussionmentioning
confidence: 90%
“…17β-estradiol treatment has been shown to suppress MCP-1 protein and gene expression in ovariectomised (OVX) rabbits (32) , and oestrogen treatment has been found to attenuate vascular re-modelling by promoting the synthesis of MCP-1 mRNA in endothelial cells (33) . Moreover, it has been demonstrated that oestrogen reduces MCP-1 mRNA levels in female OVX apoE -/ -mice, thereby preventing the development of atherosclerosis (34) . On the basis of the foregoing discussion, it is thus reasonable to assume that high-dietary cholesterol of LAHC diets does not aggravate the aortic inflammatory response in either male or female ApoE -/ -mice, although there may be differences in the underlying mechanisms.…”
Section: Discussionmentioning
confidence: 99%